Critical analysis of communication strategies in public health promotion: An empirical‐ethical study on organ donation in Germany. (18th June 2020) - Hansen, Solveig Lena; Pfaller, Larissa; Schicktanz, Silke
Abstract: Given the need for organs, public organizations use social marketing strategies to increase the number of donors. Their campaigns employ a variety of moral appeals. However, their effects on audiences are unclear. We identified 14 campaigns in Germany from over the last 20 years. Our approach combined a multimodal analysis of categorized posters with a qualitative analysis of responses, collected in interviews or focus groups, of 53 persons who were either skeptical or undecided about organ donation. The combined analyses revealed that the posters failed to motivate laypersons in general to donate, and were even less effective on skeptical or undecided individuals. We explain this in terms of the types of moral messages found on posters and the limits of such social marketing strategies. Furthermore, we discuss certain ethical aspects of organ donation campaigns pertaining to communicating norms and trust in public institutions.